Impact of Tumor Side on Clinical Outcomes in Stage II and III Colon Cancer With Known Microsatellite Instability Status - Akce, Mehmet; Zakka, Katerina; Jiang, Renjian; Williamson, Shayla; Alese, Olatunji B.; Shaib, Walid L.; Wu, Christina; Behera, Madhusmita; El-Rayes, Bassel F. (Frontiers in Oncology, 2021)
Background: Tumor sidedness as a prognostic factor in advanced stage colon cancer (CC) is well established. The impact of tumor sidedness on the clinical outcomes of stage II and III CC has not been well studied. Methods: The National Cancer Database (NCDB) was utilized to identify patients with pathological stage II and III primary adenocarcinoma of the colon from 2010-2015 using ICD-O-3 morphology and topography codes: 8140-47, 8210-11, 8220-21, 8260-63, 8480-81, 8490 and C18.0, 18.2,18.3, 18.5,18.6, 18.7. Univariate (UVA) and multivariable (MVA) survival analyses, and Kaplan-Meier Curves with Log-rank test were utilized to compare overall survival (OS) based on tumor location and treatment received. Results: A total of 35,071 patients with stage II (n=17,629) and III (n=17,442) CC were identified. 51.3% female; 81.5% Caucasian; median age 66 (range, 18-90). Majority of stage II and III tumors were R, 61.2% (n=10,794) and 56.0% (n=9,763). Microsatellite instability high (MSI-H) was more common in stage II compared to III, 23.3% (n=4,115) vs 18.2% (n=3,171) (p<0.0001). In stage II MSI-H CC right (R) was more common than left (L), 78.3 % (n=3223) vs 21.7% (n=892). There was no significant difference in survival between stage II MSI-H left vs right (5-year OS 76.2% vs 74.7%, p=0.1578). Stage II MSS CC right was more common than left, 56.0% (n=7571) vs 44.0% (n=5943), and survival was better in left vs right (5-year OS 73.2% vs 70.8%, p=0.0029). Stage III MSI-H CC was more common in right than left, 75.6% (n=2397) vs 24.4% (n=774) and survival was better in left (5-year OS 62.5% vs 56.5%, p=0.0026). Stage III MSS CC was more common in right than left, 51.6% (n=7366) vs 48.4% (n=6905), and survival was better in left vs right (5-year OS 67.0% vs 54.4%, p<0.001).